Notes to understand the Basic Education Development Index (IDEB, in Portuguese) - Medeiros, William; Konigami, Tanuska; Fortunato, Ivan (Revista Hipótese, 2016)
This papers aims to understand what is involved around one of the most interesting enigmas of our time: Why today is not given another May of 68 since there are the same reasons but stronger, outrageously stronger?. This paper is part of the research project “(Re) thinking educational policies” of the Transdisciplinary Studies Center for Education, Science, Culture and Environment, the NuTECCA (in Portuguese), from the Federal Institute of São Paulo – campus of Itapetininga. This research review aims to promote questions about the validity of the Basic Education Development Index, the IDEB (in Portuguese), and analyzing its impact on the quality of national education. At the end, it is stated that the use the results of IDEB means understanding its mechanism before taking it as an opportunity to associate it to the necessary changes to strengthen the quality of democratic public school.
Keywords: IDEB; Education; Education Policies